116k views
4 votes
Solve for d.

–4(–3d − 3) = 6d

d =

2 Answers

4 votes

Answer:


\boxed{d = -2}

Explanation:


= > - 4( - 3d - 3) = 6d \\ \\ = >( ( - 4) * ( - 3d)) - ( - 4 * 3) = - 6d \\ \\ = > 12d + 12 = 6d \\ \\ = > 12d - 6d + 12 = 0 \\ \\ = > 6d + 12 = 0 \\ \\ = > 6d = - 12 \\ \\ = > d = - (12)/(6) \\ \\ = > d = - 2

User Khem Raj Regmi
by
4.8k points
3 votes

Answer:

d = -2

Explanation:

→Distribute the -4 to (-3d - 3)

-4(-3d - 3) = 6d

12d + 12 = 6d

→Subtract 6d from both sides:

6d + 12 = 0

→Subtract 12 from both sides:

6d = -12

→Divide both sides by 6:

d = -2

User Mohammad Banisaeid
by
5.0k points